Brand personality dimensions and their effects on customer satisfaction in Kuala Lumpur hotels / Zurinawati Mohi …[et al.] - Mohi, Zurinawati; Zaireen, Abu; Sulaiman, Maimunah (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA (UiTM), Malaysia, 2014)
Sincerity, excitement, competence, sophistication and ruggedness are the dimensions of brand personality. It is the aim of this study to apply the same dimensions on hotel brands as to test whether the dimensions would reflect the hotel’s personality and eventually affect customers’ satisfaction. Using a quantitative approach, data gathered through surveys on the guests of five-star hotels in Kuala Lumpur. Descriptive statistics, correlation analysis and regression analysis were used in this study. From the five dimensions, sincerity had higher scores, and it is believed that brand personality is adaptable to hotel brands. From this study, the hospitality industry will be benefited with the essential understanding of the brand personality impact on customers’ satisfaction.